2012
DOI: 10.1039/c1ee02490f
|View full text |Cite
|
Sign up to set email alerts
|

In situ redox functionalization of composite electrodes for high power–high energy electrochemical storage systems via a non-covalent approach

Abstract: The growing demand for new global resources of clean and sustainable energy emerges as the greatest challenge in today's society. For numerous applications such as hybrid vehicles, electrochemical storage systems simultaneously require high energy and high power. For this reason, intensive researches focus on proposing alternative devices to conventional Li battery and supercapacitors. Here, we report a proof of concept based on non-covalent redox functionalization of composite electrodes that may occur either… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 52 publications
(55 reference statements)
3
40
0
Order By: Relevance
“…Moreover, the low grafting loading found for our CDC substrate is consistent with the work of Isikli et al who reported small loadings of 0.75 wt% and 0.55 wt% for loosely bonded 1,4,9,10-anthracenetetraone on PICA and Vulcan carbons, respectively, through same chemical route [53]. Hence, it is expected that AQ molecules are more likely adsorbed at the CDC surface via physisorption mechanisms through p-stacking between the aromatic rings of AQ and graphitic planes [54]. Another main problem may be the accessibility of AQ molecules to the porosity of CDC.…”
Section: à2supporting
confidence: 79%
“…Moreover, the low grafting loading found for our CDC substrate is consistent with the work of Isikli et al who reported small loadings of 0.75 wt% and 0.55 wt% for loosely bonded 1,4,9,10-anthracenetetraone on PICA and Vulcan carbons, respectively, through same chemical route [53]. Hence, it is expected that AQ molecules are more likely adsorbed at the CDC surface via physisorption mechanisms through p-stacking between the aromatic rings of AQ and graphitic planes [54]. Another main problem may be the accessibility of AQ molecules to the porosity of CDC.…”
Section: à2supporting
confidence: 79%
“…Our group recently reported a strategy for in situ graing (here onwards the term graing indicate the non covalent p stacking of pyrene molecules) of such pyrene derivatives onto a carbon ber electrode using a conventional electrolyte. 6 This approach offers enormous advantages with respect to upscaling considerations because it does not impose any change in electrode chemistry protocols, as opposed to those incurred by ex situ chemistries involving pyrene units, as reported by other researchers. 19 Considering that the adsorption 20 of polycyclic pyrene from the electrolyte is driven by p-p interactions, the graphitization state of the carbon substrate 21 is obviously a critical parameter.…”
Section: Introductionmentioning
confidence: 93%
“…Therefore, it is of great interest and significance to increase the capacitance of the carbon-based electrode in order to increase the total device capacity and concomitantly the specific energy. Immobilization of electroactive molecules which could exchange more than one electron at the carbon surface is a promising approach to achieve this aim [36]. Redox reactions of these molecules will add a Faradaic contribution to the double layer capacitance of carbon and subsequently increase the total capacity of the carbon-based electrode (Scheme 1c and 1d).…”
Section: Electrochemical Characterization Of Carbon-based and Ni(oh) mentioning
confidence: 99%